2012
DOI: 10.1093/cid/cis488
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prognosis of Hospitalization for Pneumonia Among Individuals With and Without Functioning Renal Transplants in Denmark: A Population-Based Study

Abstract: The risk of first-time hospitalization for pneumonia remains high among renal transplant candidates and recipients. The attributable morbidity and mortality are of great clinical and public health concern and preventive measures are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
5
1
2
Order By: Relevance
“…Chuang et al and Dantes et al found receiving an organ transplant from deceased donor was independently associated with an increased risk of post-transplant UTI. However, we did not find this association in our present study or in previous studies looking at infection-risk in transplant recipients [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Chuang et al and Dantes et al found receiving an organ transplant from deceased donor was independently associated with an increased risk of post-transplant UTI. However, we did not find this association in our present study or in previous studies looking at infection-risk in transplant recipients [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…27,28 This is supported by the epidemiological evidence that patients with weakened immune systems, (e.g. transplant) do not, generally, have greatly increased mortality from severe infection [29][30][31] , and the evidence of benefit of steroids in infections like COVID-19. 32 It is therefore possible that microbial load is not that relevant to outcomes in a relatively elderly cohort with bloodstream infection.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 93%
“…When comparing the relative risk of pneumonia in this population with that in others, kidney transplant recipients are at much higher risk for hospitalization for pneumonia than the general population. This is illustrated in a study from Denmark that showed that the risk for first-time hospitalization for pneumonia was eightfold higher in kidney transplant recipients than in age-matched controls (2).…”
Section: Discussion Of Question 1amentioning
confidence: 99%